Causal nexus between foreign direct investment and economic growth: A study of BRICS nations using VECM and Granger causality test. Issue 2 (1st August 2016) - Gupta, Priya; Singh, Archana
Abstract : Purpose: – The purpose of this paper is to determine cause and effect relationship between foreign direct investment (FDI) and economic growth (gross domestic product (GDP) taken as proxy) for Brazil, Russia, India, China and South Africa (BRICS nations) individually for the period 1992-2013. Also, the study tries to explore the reasons behind the linkage between FDI and GDP by estimating a linear regression model consisting of both macro-economic and institutional variables. Design/methodology/approach: – Johansen cointegration technique followed by vector error correction model (VECM) and standard Granger causality test are employed to investigate the causal linkage between FDI and GDP. To delve into the reasons behind this linkage, an ordinary least square (OLS) technique is also applied to test the linear regression model consisting of net FDI inflows as dependent variable and nine macro- economic and institutional variables. Residual diagnostics is also conducted using Breusch-Godfrey Lagrange Multiplier test for diagnosing the problem of serial correlation, Breusch-Pagan-Godfrey test for examining heteroskedasticity and Jarque Bera test for verifying the normality of residuals. Findings: – The Johansen cointegration result establishes a single cointegrating vector (long run relationship) between FDI and GDP for India, China and Brazil. After proving a cointegration, VECM results revealed that there exists unidirectional long run causality running from GDP to FDI in case of Brazil, India and China. Also, it is confirmed that there exists short run causality between FDI and GDP in China, i.e. the past lags of FDI jointly impact the value of GDP. However, for Russia and South Africa, where there is no cointegration in the long run, standard Granger causality test is conducted which reveals that in both the nations, FDI and GDP are independent of one another. The results of OLS technique reveal different country-specific factors causing this linkage between FDI inflows and economic growth. Originality/value: – Various researchers in the past have examined this issue of linkage between FDI and GDP in the context of various developing or developed nations. This reveals a gap in the existing literature pertaining to this causal linkage in the context of the BRICS. Thus, this study fills this gap by analyzing not just this causal nexus with the help of VECM and Granger causality techniques but also tries to explore further the reasons for such strong/weak/no link with the help of fitting a regression model which comprises of both macro-economic and institutional country-specific variables influencing this causation.